Implementation of Problem-Based Learning (PBL) Model Assisted by Video Media to Improve Civics Learning Outcomes at Junior High School - Damayanti, Erika Aulia; Mediatati, Nani (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This Classroom Action Research aims to improve Civic Education learning outcomes through the implementation of problem-based learning (PBL) models assisted by video media. The research subjects for class IX G SMP N 2 Ampeltotaled 32 students. Observation and tests as data collection techniques, and comparative descriptive techniques as data analysis techniques. This study used two cycles. In cycle 1, the teacher applied learning using the problem based learning (PBL) model assisted by video media, and then in cycle 2, the teacher gave evaluation questions. The results of the study concluded that learning PPKn with the problem-based learning (PBL) model assisted by video media can improve student learning outcomes. This is shown by an increase in student learning outcomes in each cycle. In the pre-cycle, 14 students (43.75%) completed KKM ≥ 75 and an average score of 69.59. In cycle 1, 21 students (65.62%) completed, and 11 students (34.38%) did not complete, and the average value was average 78.28. Then in cycle 2 increased by 32 students (100%) completed and the average value of 82.25. This research succeeded in achieving a success indicator of 100%. Therefore teachers are advised to use problem-based learning (PBL) models assisted by video media in order to improve student learning outcomes.